Interacting quantum mixtures for precision atom interferometry. (11th December 2020) - Corgier, Robin; Loriani, Sina; Ahlers, Holger; Posso-Trujillo, Katerine; Schubert, Christian; Rasel, Ernst M; Charron, Eric; Gaaloul, Naceur
Abstract: We present a source engineering concept for a binary quantum mixture suitable as input for differential, precision atom interferometry with drift times of several seconds. To solve the non-linear dynamics of the mixture, we develop a set of scaling approach equations and verify their validity contrasting it to the one of a system of coupled Gross–Pitaevskii equations. This scaling approach is a generalization of the standard approach commonly used for single species. Its validity range is discussed with respect to intra- and inter-species interaction regimes. We propose a multi-stage, non-linear atomic lens sequence to simultaneously create dual ensembles with ultra-slow kinetic expansion energies, below 15 pK. Our scheme has the advantage of mitigating wave front aberrations, a leading systematic effect in precision atom interferometry.